Emergent Role of IFITM1/3 towards Splicing Factor (SRSF1) and Antigen-Presenting Molecule (HLA-B) in Cervical Cancer - Gómez-Herranz, Maria; Faktor, Jakub; Yébenes Mayordomo, Marcos; Pilch, Magdalena; Nekulova, Marta; Hernychova, Lenka; Ball, Kathryn L; Vojtesek, Borivoj; Hupp, Ted R; Kote, Sachin (Biomolecules, 2022)
The IFITM restriction factors play a role in cancer cell progression through undefined mechanisms. We investigate new protein-protein interactions for IFITM1/3 in the context of cancer that would shed some light on how IFITM1/3 attenuate the expression of targeted proteins such as HLA-B. SBP-tagged IFITM1 protein was used to identify an association of IFITM1 protein with the SRSF1 splicing factor and transporter of mRNA to the ribosome. Using in situ proximity ligation assays, we confirmed a predominant cytosolic protein-protein association for SRSF1 and IFITM1/3. Accordingly, IFITM1/3 interacted with HLA-B mRNA in response to IFNγ stimulation using RNA-protein proximity ligation assays. In addition, RT-qPCR assays in IFITM1/IFITM3 null cells and wt-SiHa cells indicated that HLA-B gene expression at the mRNA level does not account for lowered HLA-B protein synthesis in response to IFNγ. Complementary, shotgun RNA sequencing did not show major transcript differences between IFITM1/IFITM3 null cells and wt-SiHa cells. Furthermore, ribosome profiling using sucrose gradient sedimentation identified a reduction in 80S ribosomal fraction an IFITM1/IFITM3 null cells compared to wild type. It was partially reverted by IFITM1/3 complementation. Our data link IFITM1/3 proteins to HLA-B mRNA and SRSF1 and, all together, our results begin to elucidate how IFITM1/3 catalyze the synthesis of target proteins. IFITMs are widely studied for their role in inhibiting viruses, and multiple studies have associated IFITMs with cancer progression. Our study has identified new proteins associated with IFITMs which support their role in mediating protein expression; a pivotal function that is highly relevant for viral infection and cancer progression. Our results suggest that IFITM1/3 affect the expression of targeted proteins; among them, we identified HLA-B. Changes in HLA-B expression could impact the presentation and recognition of oncogenic antigens on the cell surface by cytotoxic T cells and, ultimately, limit tumor cell eradication. In addition, the role of IFITMs in mediating protein abundance is relevant, as it has the potential for regulating the expression of viral and oncogenic proteins.
Keywords: Female; isoform of serine and arginine-rich splicing factor 1 (SRSF1); serin-arginin sestřihové faktory; ženské pohlaví; RNA Splicing Factors; proteiny vázající RNA; interferon-induced transmembrane 1 and 3 (IFITM1/3); lidé; ribosome; membránové proteiny; sestřihové faktory; HLA-B antigeny; messenger RNA; nádory děložního čípku; diferenciační antigeny; RNA, Messenger; interferon (IFN); Antigens, Differentiation; RNA-Binding Proteins; Membrane Proteins; Uterine Cervical Neoplasms; mRNA; Serine-Arginine Splicing Factors; HLA-B Antigens; Humans